First record of jaguar (Panthera onca) and potential prey species in Sierra de Quila, Jalisco, Mexico - Moreno-Arzate, Efren; Ignacio Iniguez-Davalos, Luis; Servin, Jorge; Magdalena Ramirez-Martinez, Maria; Ribeiro, Milton Cezar [UNESP]; Sevilla, Rafael (Brigham Young Univ, 2022)
The jaguar (Panthera onca) is considered a keystone species for neotropical ecosystems. Jaguar records in natural protected areas (NPAs) are important to manage and maintain the long-term occupancy of the species in a region. The objectives of this study are to report the first jaguar records in the Sierra de Quila, Jalisco, Mexico, and to report observations of potential prey items. Between February 2018 and January 2019, 24 camera traps were placed for 180 days during 3 seasons, with a total capture effort of 3216 trap nights. Four hundred and two independent records were obtained from 17 species of wild mammals and 3 domestic species. In February, 2 photographs of a jaguar were recorded at a single sampling point in the Sierra de Quila Flora and Fauna Protection Area. They correspond to the same individual, presumably an adult male. Subsequently, in July, a photograph of a jaguar was recorded at another sampling point. These records represent a 69-km extension of the known jaguar distribution, to the center of Jalisco, and increase the number of mammal species known for this NPA.